From Reading to Healing : Teaching Medical Professionalism through Literature - Blackie, Michael; Stagno, Susan (Book collections on Project MUSE., 2019)
Learning how to behave and engage professionally can be one of the most challenging parts of embarking on a career in the medical field. This expansive anthology demonstrates how medical professionals can powerfully engage with their students through a variety of literary texts for discussion and inspiration.